Organocatalytic enantioselective approach to the synthesis of verbalactone and (R)-massoialactone - Harbindu, Anand; Kumar, Pradeep (Synthesis-Stuttgart, 2011)
The organocatalytic enantioselective synthesis of verbalactone and (R)-massoialactone is described. The requisite stereogenic centers of the target molecules were constructed using L-proline-catalyzed alpha-aminoxylation and Horner-Wadsworth-Emmons (HWE) olefination. Yamaguchi macrolactonization and ring-closing metathesis were employed as key steps in the syntheses.
Keywords: alpha-aminoxylation; Horner-Wadsworth-Emmons olefination; L-proline; massoialactone; Ring-closing metathesis; verbalactone; Yamaguchi macrolactonization